The Mask And The Language Of Staging At The Venice Carnaval (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This article presents the mask as a staging language and symbolic costume, focusing on its presence as a scenic element in the Venice Carnival. It addresses the transition of the mask from Commedia Dell'Arte to popular festivities in 16th century Italy, as well as its continuity as part of the characterization of revelers over the years in Venice. Based on the historiographical method, it constitutes a reflection on the formation of cultural memory as an expressive social phenomenon related to understanding the presence of the mask as a scenic prop in Western culture, both in the performing arts and in popular culture.
Keywords: theatrical design; theatrical masks; venice carnival